PARADOKS KEHARMONISAN KELUARGA DALAM FILM NGERI-NGERI SEDAP KARYA BENE DION RAJAGUKGUK - Dian Alfianti; Desti Lestari; Mardiana Lipa; Saptiana Sulastri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the paradox of family harmony in the film Ngeri-Ngeri Sedap by Bene Dion Rajagukguk. The main issue in this research is how the family harmony that appears on the surface actually conceals conflicts, tensions, and emotional distance among family members. The aim of this study is to reveal the forms of the harmony paradox and interpret its meaning in the context of family relationships. This study uses a qualitative descriptive method with a content analysis approach, which focuses on narrative elements, dialogues, and interactions among the characters in the film. Data collection was conducted through non-participant observation by repeatedly and thoroughly watching the film, as well as documentation techniques in the form of recording dialogues, scenes, and interactions relevant to the research focus. The obtained data were then analyzed interpretatively to understand the communication dynamics and family relationships depicted. The research results indicate that family harmony in the film is built through cultural demands, non-open communication patterns, and the dominance of parental authority, which tends to suppress emotional expression and individual desires. This condition creates a paradox, where harmony appears to be maintained on the surface, but conflict continues to occur secretly through dialogue and interactions between characters. This study concludes that the film reflects the complexity of maintaining family integrity, especially in cultures that prioritize togetherness over openness, so true harmony requires honest communication and mutual understanding.